Insights on therapeutic potential of clemastine in neurological disorders - Jiang, Sufang; Wang, Xueji; Cao, Tianyu; Kang, Rongtian; Huang, Lining (Frontiers in Molecular Neuroscience, 2023)
Clemastine, a Food and Drug Administration (FDA)-approved compound, is recognized as a first-generation, widely available antihistamine that reduces histamine-induced symptoms. Evidence has confirmed that clemastine can transport across the blood–brain barrier and act on specific neurons and neuroglia to exert its protective effect. In this review, we summarize the beneficial effects of clemastine in various central nervous system (CNS) disorders, including neurodegenerative disease, neurodevelopmental deficits, brain injury, and psychiatric disorders. Additionally, we highlight key cellular links between clemastine and different CNS cells, in particular in oligodendrocyte progenitor cells (OPCs), oligodendrocytes (OLs), microglia, and neurons.